1998
DOI: 10.1074/jbc.273.26.16382
|View full text |Cite
|
Sign up to set email alerts
|

A Binding Site for Heparin in the Apple 3 Domain of Factor XI

Abstract: Since heparin potentiates activated factor XI (FXIa) inhibition by protease nexin-2 by providing a template to which both proteins bind (Zhang, Y., Scandura, J. M., Van Factor XI (FXI) 1 is a zymogen that circulates in plasma in a non-covalent complex with high molecular weight kininogen (HMWK) (1, 2) and participates in the contact phase of blood coagulation (3). The active enzyme, activated factor XI (FXIa), is a trypsin-like serine protease that is generated when FXI is cleaved by FXIIa (3), thrombin, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 42 publications
3
93
3
Order By: Relevance
“…Due to its binding to the forming thrombus in vivo, cell-free RNA may become concentrated at these sites and serves as cofactor for protease activation. Cellular binding sites for factors XII and XI (32,33) could be shared by RNA, and heparin may compete for factor XII/XI binding to RNA, thereby providing an alternate mechanism of anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its binding to the forming thrombus in vivo, cell-free RNA may become concentrated at these sites and serves as cofactor for protease activation. Cellular binding sites for factors XII and XI (32,33) could be shared by RNA, and heparin may compete for factor XII/XI binding to RNA, thereby providing an alternate mechanism of anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the defect in binding characterizing these mutants is exclusively due to their ability to interact with platelet membranes. As positive controls, we used the mutants K252A and K253A, which showed normal platelet binding but abnormal heparin binding (32); these mutants demonstrated normal HK and platelet binding. This further solidifies our contention that FXI platelet binding is specific and is mediated by specific amino acid residues Ser 248 , Arg 250 , Lys 255 , Leu 257 , and Gln 263 .…”
Section: The Effects Of Mutant Recombinant Factor XI Proteins In Coagmentioning
confidence: 99%
“…In addition FXI apple A1 binds to thrombin (42), an important endogenous activator of FXI in blood coagulation (43,44). FXI domain A3 has been shown to bind to platelets (45) and heparin (46), and domain A4 to FXIIa (47). Using a synthetic peptide approach Walsh and co-workers (48) demonstrated that FXI domain A2 binds FIX although this conclusion has been challenged by the recent study of Sun and Gailani (30) who used recombinant FX-PPK chimeras to show that the FIX-binding site is located in A3 rather than in A2.…”
Section: Fig 5 Transfer Of Ppk Apple Domain A2 Increases Hk Bindingmentioning
confidence: 99%